Lomban Jepara Sebagai Inspirasi Penciptaan Film - Philipus Nugroho Hari Wibowo (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
The creation of this film inspiring on the idea of the Lomban ceremony in Jepara Regency. Lomban is a buffalo head barrel ritual in the middle of the sea as an expression of gratitude. The creation of Andini’s Dream combines fiction film and Visual data from Lomban Research packed with a visual anthropological approach. The Lomban story is presented with the perspective of a woman named Andini, a sad buffalo owner who lost her buffalo because it was used for the Lomban ceremony.